Factors affecting bond strength between acrylic dental elements and thermoplastic nylon bases: a systematic literature review - Denny Adhinugroho Suciptoi; Henny Pratiwi Adi; Prabowo Setiyawan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The Transit Oriented Development Tanjungbarat Apartment Project is part of Perumnas' initiative to provide vertical housing integrated with public transportation. However, this project faces various challenges due to project risks, such as permitting issues, resource limitations, financial constraints, and other external factors. This study aims to analyze the influence of various types of risks on project success, assess risk probability and impact, and evaluate the risk mitigation strategies implemented by Perum Perumnas.The research employs a quantitative method with a case study approach. Data is collected through literature reviews, questionnaires, and interviews. The questionnaire respondents consist of 32 individuals, including the Project Management Office, project leaders, risk management, project structure, construction management, and construction executors involved in the TOD Tanjung Barat Apartment Project. The questionnaire results undergo validity and reliability testing, followed by multiple regression analysis. The identified risk variables are assessed using a risk scale formula (Probability × Impact) on a risk map to determine risk levels.The research findings indicate that the highest risk levels originate from resource-related aspects (4.08), design (4.06), environmental factors (4.06), financial aspects (3.72), and construction (3.87), all of which significantly impact project success. The risk matrix evaluation reveals that the project faces 4 risks at a high level, 7 at a moderate to high level, 6 at a moderate level, 8 at a low to moderate level, and 3 at a low level. The implemented risk mitigation strategies have proven effective in reducing risk levels, particularly for high-risk categories, contributing to the success of the Transit Oriented Development Tanjungbarat Project. However, continuous risk management is necessary to prevent risk escalation, especially for future project